2022
DOI: 10.1093/icvts/ivac095
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of surgical revascularization in patients with reduced left ventricular ejection fraction—a population-based cohort study

Abstract: Background Surgical revascularization is an established indication for patients with advanced coronary artery disease and reduced left ventricular ejection fraction (LVEF). Long-term outcomes for these patients are not well defined. We studied the long-term outcomes of patients with ischaemic cardiomyopathy who underwent surgical revascularization in a well-defined nationwide cohort. Materials and methods A retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Yoo et al [18] assessed 476 patients with an LVEF ≤ 35 % who underwent CABG and demonstrated that ≥ moderate MR, lower eGFR, and LV wall thinning were independent predictors of death. Likewise, Hillis et al showed that higher age and lower eGFR are strong predictors of mortality in reduced LVEF (≤35) [19] , which was comparable to the results of a study by Brynjarsdottir et al including advanced age, DM, chronic kidney disease (CKD), COPD, current smoking, NYHA classification III or IV, emergency procedure and longer skin-to-skin time [11] . In a similar study by DeRose et al, higher age, PVD, emergency operation, and chronic obstructive pulmonary disease were independent predictors of higher mortality in patients with LVEF ≤ 25 [20] .…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Yoo et al [18] assessed 476 patients with an LVEF ≤ 35 % who underwent CABG and demonstrated that ≥ moderate MR, lower eGFR, and LV wall thinning were independent predictors of death. Likewise, Hillis et al showed that higher age and lower eGFR are strong predictors of mortality in reduced LVEF (≤35) [19] , which was comparable to the results of a study by Brynjarsdottir et al including advanced age, DM, chronic kidney disease (CKD), COPD, current smoking, NYHA classification III or IV, emergency procedure and longer skin-to-skin time [11] . In a similar study by DeRose et al, higher age, PVD, emergency operation, and chronic obstructive pulmonary disease were independent predictors of higher mortality in patients with LVEF ≤ 25 [20] .…”
Section: Discussionmentioning
confidence: 55%
“…Generally, higher five-year mortality rates have been reported across the literature, varying significantly from 20 % to 40 % [4] , [28] , [29] . Moreover, Brynjarsdottir et al reported 38 % five-year MACCE for patients with LVEF ≤ 35 [11] . Most studies have evaluated only mortality risk without investigating the adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation